Bridging education and CSR: the role of corporate foundations in Malaysia’s human capital development - Mohd Radzi, Naziatul Aziah; Lee, Khai Ern; Abdul Halim, Sharina; Siwar, Chamhuri; Azman Aziz, Mukhriz Izraf (Institute of Advanced Engineering and Science, 2025)
The outlined target in sustainable development goals (SDG) relating to educational aspects indicates that education plays an important role and should become the primary concern of various parties. Hence, this study focused on the implications of corporate social responsibility (CSR) in educational aspects towards the development of human capital from the viewpoints of selected corporate foundations in Malaysia. This study was conducted through a questionnaire survey in which data were analyzed using IBM SPSS Statistics 20 software. The target population for this study were individuals involved with CSR initiatives conducted by four selected corporate foundations which are the implementers and students who received assistance from corporate foundations. The analysis shows that educational activities in CSR initiatives undertaken by corporate foundations have helped in the development of human capital. Both implementers and recipients give priority to scholarship sponsorships followed by school assistance, organizing workshops and seminars as valuable activities for individuals. The CSR initiatives in educational aspects have highlighted the role of corporate foundations as agents that can help individuals to achieve their dreams of pursuing tertiary education. The involvement of corporate foundations in education has created value for companies and certainly for society, in which corporate foundations have established relationships with stakeholders, as explained in the stakeholder theory.